Penerapan Kompres Jahe Hangat Pada Lansia Dengan Nyeri Sendi - Indra Wijaya; Asep Widi Solih Setiawan; Rina Libranty; Mei Putri Crismayanti (Jurnal Kesehatan Bhakti Husada, 2026)
Joint pain is a common health problem in the elderly and can reduce quality of life and the ability to perform daily activities. One non-pharmacological intervention that can be used is a warm ginger compress, which has an anti-inflammatory effect and provides a warm sensation to reduce pain. This study aims to determine the application of warm ginger compresses in reducing joint pain in the elderly. The research design used a descriptive method with a case study approach through nursing care. The population was elderly people with joint pain in Bulusari Village, Sayung, Demak, with a sample of 2 respondents selected using a purposive sampling technique. Data collection techniques were carried out through interviews, observations, and physical examinations with pain scale measurements before and after the intervention. The warm ginger compress intervention was given for 3 days, each for 20 minutes. The results showed a decrease in the pain scale in both respondents, where the first respondent experienced a decrease from a scale of 7 to 5, and the second respondent from a scale of 5 to 2. This indicates that warm ginger compresses are effective in reducing the intensity of joint pain in the elderly. The conclusion of this study is that warm ginger compresses can be used as a simple and effective non-pharmacological therapy to reduce joint pain. It is recommended that families and healthcare professionals utilize this therapy as an alternative treatment for joint pain in the elderly, and that future researchers conduct studies with larger sample sizes and more robust methods